Effectiveness of a planned teaching program regarding modified bass brushing technique on knowledge among school children at selected school of rural area of Lucknow district - Macknight, Shweta; Kumar, Rohitash; Singh, S. K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Pre-schooler are very much prone to infectious diseases due to low immunity among those diseases the commonest is dental carries which occurs due to improper brushing technique. The study was conducted with the objective to assess knowledge and effectiveness of planned teaching program regarding modified bass brushing technique among school children at selected rural area. Methods: Research design and setting experimental pre-test-post-test control group design used and setting was selected rural area, Sarojini Nagar, Lucknow, Uttar Pradesh. Sample and sampling technique total 66 sample and villages for experimental and control group were selected through simple random technique. Tools were used as self-structured knowledge questionnaire and checklist. Results: Revealed that in experimental group post-test mean and SD score (7.55±1.09) was significantly higher than pre-test score (5.06±1.03) and in checklist the post-test mean and SD score (7.64±1.32) was significantly higher than the mean and SD pre-test score was 5.27±0.45. The researcher compared the calculated t-value (11.04) with the tabulated value (1.986) for the questionnaire and the checklist t-value 3.14. In control group the knowledge questionnaire post-test mean and SD score was (5.27±0.45) and pre-test mean and SD score was (4.24±1.03) with the t-value of 0.04. Whereas checklist post-test mean and SD score (5.21±0.48) and pre-test mean and SD score (5.27±0.05) with the t- value 0.32. Conclusions: Thus the planned teaching programme on knowledge regarding modified bass brushing technique was effective.